Quantitative determination of dexamethasone sodium phosphate in bulk and pharmaceuticals at suitable pH values using the spectrophotometric method - Mohammed Fanokh Al-Owaidi; Sura L Alkhafaji; Abdulbari Mahdi Mahood (Wolters Kluwer Medknow Publications, 2021)
Dexamethasone sodium phosphate (DSP) is an ester of dexamethasone with anti-inflammatory action. This study provides new insights to develop a simple, precise, and accurate spectrophotometric method for the quantitative determination of DSP in bulk and pharmaceuticals. The method was validated before being applied to determine the DSP in six pharmaceutical injection forms from different companies. DSP is soluble in phosphate buffer, so it was used as a solvent, and a pH of 6 was found to be suitable for determination purposes. The DSP solution was scanned in the ultraviolet range (200-400 nm) using a double-beam spectrophotometer with a 1-cm quartz cell. The wavelength (λ max) of DSP was set at 242.5 nm, following the Beer-Lambert law for concentrations from 2 to 50 μg/ml. Dexa AIWA (Germany) showed the best results, being very close to the bulk value with no significant variation. Similarly, Dexamed (Cyprus) and HEMAZON (Syria) showed no significant differences from the bulk; however, the three remaining injections, DEXAKAL (India), DEXABRU (India), and DEXARON (China), showed significant variations from the bulk. Estimated limit of detection and limit of quantitation values for DSP were 0.83 and 2.5 μg/ml, respectively, with a regression coefficient of 0.999. Recovery studies were then used to determine the accuracy of the suggested method. The percentage of recovery was found to be 98.58%-102.52%. All results are suggesting a pivotal method for the routine analysis of DSP both in pure form and the commercially pharmaceutical forms.